Iowa Birdline update, December 21, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for December 21, 1992. The highlights for the update include sightings from several Christmas counts including a Great Black-backed Gull, 17 Eurasian Tree Sparrows, four Northern Goshawks and five Yellow-rumped Warblers. Also included are handwritten notes with sightings of a Snowy Owl, an immature and adult Pine Warbler associating with Golden-crowned Kinglets. Epson - sheet feed/flatbed